Improved-high-quality draft genome sequence of Rhodococcus sp. JG-3, a eurypsychrophilic Actinobacteria from Antarctic Dry Valley permafrost. Issue 1 (December 2015) - Goordial, Jacqueline; Raymond-Bouchard, Isabelle; Ronholm, Jennifer; Shapiro, Nicole; Woyke, Tanja; Whyte, Lyle; Bakermans, Corien
Abstract The actinobacteriumRhodococcus sp . JG-3 is an aerobic, eurypsychrophilic, soil bacterium isolated from permafrost in the hyper arid Upper Dry Valleys of Antarctica. It is yellow pigmented, gram positive, moderately halotolerant and capable of growth from 30 °C down to at least −5 °C. The 5.28 Mb high-quality-draft genome is arranged into 6 scaffolds, containing 9 contigs and 4998 protein coding genes, with 64 % GC content. Increasing the availability of genome sequences from cold-adapted species is crucial to gaining a better understanding of the molecular traits of cold adaptation in microbes.